Asymptomatic left ventricular dysfunction in patients with type 2 diabetes free of cardiovascular disease and its relationship with clinical characteristics: The DIACAR cohort study. Issue 2 (24th November 2020) - Antakly‐Hanon, Yara; Ben Hamou, Adrien; Garçon, Philippe; Moeuf, Yoann; Banu, Isabela; Fumery, Maxime; Voican, Adela; Abassade, Philippe; Oriez, Constance; Chatellier, Gilles; Dupuy, Olivier; Cador, Romain; et al.
Abstract: Aims: To assess the prevalence, type and clinical factors associated with left ventricular (LV) dysfunction in patients with type 2 diabetes mellitus (T2DM) by performing a comprehensive echocardiographic Doppler assessment including speckle tracking. Methods: Two hundred T2DM patients without overt cardiovascular disease were prospectively enrolled in a single‐centre cohort study between 2018 and 2019. Results: Left ventricular mass was increased in 24 patients (12%) and relative wall thickness (h/r) was increased in 46 patients (23%). Left atrial (LA) enlargement was observed in 27 patients (13.6%) and global longitudinal strain (GLS) was reduced in 38 patients (20.3%). In univariate analysis, LV hypertrophy (LVH) or increased h/r were associated with age, renal function, hypertension and B‐type natriuretic peptide (BNP) plasma level. LA dilation was associated with age, history of hypertension, diabetes duration and complications, insulin treatment, BNP level and renal function. GLS was associated with body mass index (BMI) and, in a borderline manner, with diabetes duration. In multivariate analysis, hypertension was associated with LVH and with h/r and a borderline relationship was observed for female gender (LVH), age and insulin treatment (h/r). Age, hypertension and, in a borderline manner, insulin treatment were associated with LA dilation. BMI and shorter diabetes duration were associated with reduced GLS. Conclusion: A high prevalence of asymptomatic cardiac dysfunction/structural abnormalities was observed in patients with T2DM without overt cardiac disease and was associated with either age, diabetes duration or treatment and with comorbidities including hypertension and obesity. Whether these preclinical abnormalities are associated with poor outcomes warrants further study.